Ecosystem Services and Human Wellbeing-Based Approaches Can Help Transform Our Economies - Sangha, Kamaljit K.; Gordon, Iain J.; Costanza, Robert (Frontiers in Ecology and Evolution, 2022)
Despite wider recognition of human interdependence with the rest of nature, our economies continue to fail to adequately value ecosystem services. This failure is largely attributed to the economic frameworks and related measures that focus on production and consumption of marketed goods and services, but do not consider the other essential elements upon which our lives depend. This paper highlights how the Ecosystem Services approach can shift the focus to human well-being while remaining within biophysical planetary boundaries. An Ecosystem Services approach applies three fundamental principles of Ecological Economics: sustainable scale, efficient allocation, and fair distribution, which are vital for sustainable economies and societies. We provide case studies from both a local and national scale demonstrating how such an approach offers a holistic perspective of understanding what ‘development’ actually means. Transforming our economies to appropriately consider planetary limits, overcome societal addictions, learn from Indigenous and local communities sustainable ways of living, and realise the importance of ecosystem services will contribute to developing economies that are resilient, and enhance sustainable human well-being.